Trial of Labour after Caesarean Section in Sub-Saharan Africa: A systematic review and meta-analysis - Boatin, Adeline; Garba, Deen; Sawyer, Michala; James, Kaitlyn; Ngonzi, Joseph; Lugobe, Henry; Wylie, Blair; Adu-Bonsa oh, Kwame (Authorea Preprints, 2023)
Background: Intrapartum decision-making for women with a previous caesarean section (CS) is complex due to competing risks of trial of labour after cesarean (TOLAC) and elective repeat CS (ERCS). Objective: Determine rates of TOLAC and vaginal birth after cesarean (VBAC) in sub-Saharan Africa (SSA) and estimate rates of adverse events associated with TOLAC versus ERCS. Search Strategy: We searched PubMed, MEDLINE, CAB, EMBASE, and African-specific databases. Selection Criteria: We included studies with at least one previous CS conducted in SSA. Data Collection and Analysis: We extracted data on study design, planned and actual delivery mode, and maternal and perinatal outcomes. We calculated median TOLAC and VBAC rates pooled mean uterine rupture rate and compared uterine rupture rates and mortality between TOLAC and ERCS. Main Results: From 51 included studies, the median TOLAC and VBAC rates, weighted for sample size, were 75% (IQR: 40-100%) and 34% (IQR: 24-44%), respectively; and the weighted mean uterine rupture rate was 1.3% (SD: 1.6%). The uterine rupture rate [1.2% vs 0.2%, OR 1.54 (95% CI 0.63-3.75)] and maternal mortality [0.3% vs <0.1%, OR 0.77 (95% CI 0.30-1.98)] did not differ significantly between TOLAC and ERCS groups, respectively, however perinatal mortality was higher for the TOLAC group (5% vs 1%, OR 3.3; 95% CI 1.5-6.9) Conclusions: We found high rates of TOLAC and moderate rates of VBAC across SSA, with a perinatal but no maternal benefit to ERCS compared to TOLAC. Further research is needed to understand delivery outcomes in this population of women.
Keywords: Labour; Caesar; Women; Sub-Saharan Africa